Merkel cell carcinoma – Beast with two Backs. Issue 9 (September 2015) - Ganjre, Anjali P.; Bagul, Neeta; Sarode, Gargi
Summary Merkel cell carcinoma of cutaneous and mucosal origin shows many differences like in origin, etiology, anatomical site, prognosis etc. This communication focuses briefly on the differences between mucosal MCC and cutaneous MCC.